2023
DOI: 10.1161/circulationaha.122.063642
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Outcomes in Patients With Heart Failure: Are There Thresholds and Inflection Points in Left Ventricular Ejection Fraction and Thresholds Justifying a Clinical Classification?

Abstract: BACKGROUND: Recent guidelines proposed a classification for heart failure (HF) on the basis of left ventricular ejection fraction (LVEF), although it remains unclear whether the divisions chosen were biologically rational. Using patients spanning the full range of LVEF, we examined whether there was evidence of LVEF thresholds in patient characteristics or inflection points in clinical outcomes. METHODS: Using patient-level information, we created a mer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The finding reported herein that the risk of adverse outcomes, including all-cause mortality and all-cause hospitalization, was similar in patients with HFrEF, HFmrEF, and HFpEF, even after adjusting for confounders, is in contrast to existing literature which primarily supports that patients with HFrEF have worse clinical outcomes. 7,12,13 TRANSFORM-HF, owing to its pragmatic design and method for end point ascertainment, prespecified the use of all-cause death and allcause hospitalization, alone and in combination, as its end points. 8 Previous HF studies have mainly focused on cardiovascular mortality and HF hospitalization and have shown that HFrEF is associated with an increased risk of these compared with HFpEF, which is, in part at least, counterbalanced by the proportionally lower risk of noncardiovascular mortality and hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…The finding reported herein that the risk of adverse outcomes, including all-cause mortality and all-cause hospitalization, was similar in patients with HFrEF, HFmrEF, and HFpEF, even after adjusting for confounders, is in contrast to existing literature which primarily supports that patients with HFrEF have worse clinical outcomes. 7,12,13 TRANSFORM-HF, owing to its pragmatic design and method for end point ascertainment, prespecified the use of all-cause death and allcause hospitalization, alone and in combination, as its end points. 8 Previous HF studies have mainly focused on cardiovascular mortality and HF hospitalization and have shown that HFrEF is associated with an increased risk of these compared with HFpEF, which is, in part at least, counterbalanced by the proportionally lower risk of noncardiovascular mortality and hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…However, the more patient-relevant metric is absolute benefit. The study by Kondo et al 4 demonstrates that the absolute risk of cardiovascular death and heart failure hospitalization decreases with increasing LVEF. Thus, the relative benefit of treatment, when multiplied by the lower absolute risk, leads to less absolute benefit with SGLT2 inhibitors at a higher LVEF.…”
Section: Article See P 732mentioning
confidence: 98%
“…The study by Kondo et al 4 shows that the LVEF-outcome relationship is complex, with different thresholds for increased risk depending on the outcome. Thus, there is no clear range at which we can say the LVEF is normal (optimal health).…”
Section: Article See P 732mentioning
confidence: 99%
See 1 more Smart Citation